2022
DOI: 10.1002/aoc.6652
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and multifunctional applications of novel metal complexes based on thiazolylazo dye

Abstract: Herein, a novel ligand, namely, N,N-dimethyl-4-((4-(pyridin-2-yl)thiazol-2-yl) diazenyl)aniline, and its solid Mn (II), Co (II), Ni (II), and Cu (II) complexes have been synthesized and characterized. The photophysical properties of the thiazolyl azo ligand, L, have been investigated in various solvents of different polarities. The absorption and fluorescence maxima of the ligand show a strong dependence on the solvent polarity. The metal ions sensing response to Mn (II), Co (II), Ni (II), and Cu (II) ions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…According to Koopman’s theorem, the dyes’ E HOMO and E LUMO are connected to the ionization potential ( I ) and electron affinity ( A ), respectively . Other quantum chemical parameters that provide useful information about the reactivity of the dyes are calculated as follows , χ 0.25em ( electronegativity ) = ( E LUMO + E HOMO ) 2 μ 0.25em ( potential ) = prefix− χ = false( E normalL normalU normalM normalO + E normalH normalO normalM normalO false) 2 η 0.25em ( hardness ) = false( E LUMO E HOM normalO false) 2 ω 0.25em ( electrophilicity ) = μ 2 / 2 η Softness is defined as the inverse of global hardness, expressed as follows ( softness ) = 1 / η The fraction of electrons (Δ N ) transferred between the inhibitors and the metallic surface is expressed as follows norm...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Koopman’s theorem, the dyes’ E HOMO and E LUMO are connected to the ionization potential ( I ) and electron affinity ( A ), respectively . Other quantum chemical parameters that provide useful information about the reactivity of the dyes are calculated as follows , χ 0.25em ( electronegativity ) = ( E LUMO + E HOMO ) 2 μ 0.25em ( potential ) = prefix− χ = false( E normalL normalU normalM normalO + E normalH normalO normalM normalO false) 2 η 0.25em ( hardness ) = false( E LUMO E HOM normalO false) 2 ω 0.25em ( electrophilicity ) = μ 2 / 2 η Softness is defined as the inverse of global hardness, expressed as follows ( softness ) = 1 / η The fraction of electrons (Δ N ) transferred between the inhibitors and the metallic surface is expressed as follows norm...…”
Section: Resultsmentioning
confidence: 99%
“…According to Koopman's theorem, the dyes' E HOMO and E LUMO are connected to the ionization potential (I) and electron affinity (A), respectively. 63 Other quantum chemical parameters that provide useful information about the reactivity of the dyes are calculated as follows 64 Softness is defined as the inverse of global hardness, expressed as follows…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…The energy minimized using default parameters for field force, default triangular matcher, and rigid receptor were employed. Out of a total of 10 postures, London dG and GBVI/WSA dG were used as the scoring functions to determine the top 5 poses 33,34 …”
Section: Methodsmentioning
confidence: 99%
“…These compounds are also widely utilized in medicine, where they have shown effective as anticancer agents, antibacterial agents, antiseptics, and antineoplastics. 29 A literature survey indicated that complexes of Co(II), Ni(II), and Cu(II) with single azo or 8-hydroxyquinoline (HQ) ligand were reported to show anticancer, 30,31 antitumor, 32,33 antioxidant, 34,35 and antimicrobial activity. 36,37 Also, previous studies indicated that Co(II), Ni(II), and Cu(II) complexes based on azo-8-hydroxyquinoline derivatives exhibited good to moderate affinity to dyeing polyester fabrics 38 and promising antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%